Elastic adhesive bandage for catalyzing release of nitric oxide as well as preparation method and application of elastic adhesive bandage

Through the elastic adhesion bandage catalyzing the release of nitric oxide, it is used for external support of arteriovenous fistula, the problem of low patency rate of autologous arteriovenous fistula is solved, and the inhibition of endometrial hyperplasia and the improvement of vascular patency rate is achieved.

CN119524216APending Publication Date: 2025-02-28SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411647190.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, the patency rate of autologous arteriovenous fistula is low, mainly due to the endometrial hyperplasia and stenosis caused by increased intravascular pressure, and the presence of the external vascular stent for too long may trigger an autoinflammatory response.

Method used

An elastic adhesion bandage that catalyzes the release of nitric oxide, is provided to prepare elastic fiber membranes and ultraviolet-cured hydrogels by electrospinning, and catalyzes the release of nitric oxide in combination with selenocystamine, which is used to external support at the arteriovenous fistula, inhibit endometrial hyperplasia and improve vascular patency.

Benefits of technology

Effectively promote the maturation of arteriovenous fistula, reduce endometrial hyperplasia, improve vascular patency, and strengthen localization through local drug release, reducing the adverse effects of systemic drug administration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524216A_ABST
    Figure CN119524216A_ABST
Patent Text Reader

Abstract

The invention discloses an elastic adhesive bandage for catalyzing release of nitric oxide as well as a preparation method and application of the elastic adhesive bandage. The preparation method comprises the following steps: dissolving thermoplastic polyurethane and polycaprolactone in an organic solvent, uniformly stirring and dissolving, carrying out electrostatic spinning, and drying to obtain a TPU / PCL electrostatic spinning film; the preparation method comprises the following steps: dissolving gelatin, acrylic acid, acrylic acid N-hydroxysuccinimide ester, polyethylene glycol diacrylate and (2, 4, 6-trimethylbenzoyl) diphenyl phosphine oxide in water, stirring, adding selenocystamine, and carrying out ultraviolet curing to obtain GPS hydrogel; the GPS hydrogel and the TPU / PCL electrostatic spinning film are attached and then dried, and the elastic adhesive bandage for catalyzing release of nitric oxide is obtained. The elastic adhesive bandage for catalyzing release of nitric oxide has good mechanical properties and biocompatibility, and can catalyze a nitric oxide donor in a body to generate nitric oxide so as to inhibit migration of smooth muscle cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical devices, and in particular relates to an elastic adhesive bandage for catalyzing the release of nitric oxide, and a preparation method and application thereof. Background Art

[0002] At present, hemodialysis is the most commonly used and important blood purification method. It is an effective method for treating acute and chronic renal failure, including end-stage renal disease (ESRD) and certain acute drug and poison poisoning. During hemodialysis, a large blood flow is required to flow through the dialyzer to filter and remove toxins from the body. A stable and reliable vascular access is the basic guarantee for smooth hemodialysis. Arterial blood flow is large, but it is difficult to puncture at a deeper position in the body. It is easier to puncture the veins on the surface of the body, but it cannot provide such a large blood flow. Therefore, a better way is to arterialize the veins, anastomose the arteries and veins through surgery to create fistulas, and let part of the blood in the arteries flow directly to the veins, thereby increasing the blood flow in the veins.

[0003] There are currently three types of vascular access, namely, Arteriovenous Graft (AVG), Central Venous Catheter (CVC) and Autogenous Arteriovenous Fistula (AVF). Autogenous arteriovenous fistula has become the first choice for long-term vascular access recognized at home and abroad due to its low infection rate, repeated puncture, and stable blood flow. However, the maturity rate of fistulas in patients is low, with a 1-year patency rate of 60%-65%, and a patency rate of less than 40% within 2 years. Studies have shown that the reason for the 90% decrease in the patency rate of autogenous arteriovenous fistulas is intimal hyperplasia. After the establishment of AVF, the pressure in the veins rises from the lower venous pressure to the higher arterial pressure, and the venous wall is subjected to relatively large tension. The venous endothelial cells at the arteriovenous anastomosis are first damaged and apoptotic under the stress of arterial blood flow. In addition, surgical injuries during AVF establishment and dialysis puncture lead to the infiltration of inflammatory cells and the secretion of a large number of inflammatory mediators. Then, smooth muscle cells migrate to the intima layer and proliferate, aggregate and secrete extracellular matrix, resulting in continuous thickening of the vascular intima and stenosis of the blood vessels, which eventually leads to the failure of the arteriovenous fistula.

[0004] There are currently two types of extravascular stents, one is a metal extravascular stent and the other is a polymer extravascular stent. VasQ is a device composed of a combination of nickel-titanium alloys and is placed at the anastomosis of arteriovenous fistulas. It can guide a more stable blood flow curve when blood transitions from arteries to veins. Clinical data show that after implantation of VasQ, 90% of arteriovenous fistulas can be used for dialysis (average time is 41 days), and 84% of fistulas remain secondary patency within 3 years. However, VasQ also has defects. One of the problems is that once the vein is arterialized, the existence of the extravascular stent becomes redundant. VasQ is made of nickel-titanium alloy and is not absorbable. Unless it is removed surgically, it will remain in the patient's body for life, which may stimulate autoinflammatory reactions in the body. In addition, the specifications and models of VasQ are fixed, which means that patients can only choose the stent closest to their blood vessel size and cannot customize it according to their own conditions. On June 27, 2024, VenoStent launched the extravascular stent SelfWrap. Although the stent can be customized, the arteriovenous fistula surgery itself is relatively complicated and difficult to suture. It also cannot solve the problem of smooth muscle cells migration and proliferation to the intima layer in the later stage of application and lacks certain biological activity. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide an elastic adhesive bandage that catalyzes the release of nitric oxide and a preparation method and application thereof.

[0006] The elastic adhesive bandage for catalyzing the release of nitric oxide is used for external support of arteriovenous fistula to promote the maturation of fistula, reduce intimal hyperplasia and improve the patency of blood vessels.

[0007] The purpose of the present invention is achieved by at least one of the following technical solutions.

[0008] The present invention provides a method for preparing an elastic adhesive bandage for catalyzing the release of nitric oxide, comprising the following steps:

[0009] (1) dissolving thermoplastic polyurethane and polycaprolactone in an organic solvent, stirring and dissolving them uniformly, then electrospinning them, and drying them to obtain a TPU / PCL electrospinning membrane;

[0010] (2) dissolving gelatin, acrylic acid, acrylic acid N-hydroxysuccinimide ester, polyethylene glycol diacrylate, and (2,4,6-trimethylbenzoyl) diphenylphosphine oxide in water, adding selenocystamine after stirring, and curing with ultraviolet light to obtain GPS hydrogel;

[0011] (3) After bonding the GPS hydrogel and the TPU / PCL electrospun membrane, the membrane was dried to obtain an elastic adhesive bandage that catalyzes the release of nitric oxide.

[0012] Preferably, the mass ratio of the thermoplastic polyurethane to polycaprolactone in step (1) is (1:10) to (10:1);

[0013] Further preferably, the mass ratio of the thermoplastic polyurethane to polycaprolactone in step (1) is (1:3) to (3:1);

[0014] Preferably, the total mass percentage concentration of the thermoplastic polyurethane and polycaprolactone in step (1) is 8% to 30%.

[0015] Preferably, the electrospinning parameters of step (1) are: blunt stainless steel needle: 20G-22G; electrospinning speed: 0.5-4mL / h; collector distance: 5-30cm; voltage: 10-20kV; temperature: 10-35°C; humidity: 20-60%; collector speed: 100-1000rpm.

[0016] Preferably, the organic solvent in step (1) is hexafluoroisopropanol;

[0017] Preferably, the stirring time in step (1) is 24 to 36 hours;

[0018] Preferably, the drying temperature in step (1) is room temperature and the drying time is 24 to 36 hours; and the drying is vacuum drying.

[0019] Preferably, the mass percentage concentrations of gelatin, acrylic acid, N-hydroxysuccinimide acrylic acid, polyethylene glycol diacrylate, and (2,4,6-trimethylbenzoyl) diphenylphosphine oxide in step (2) are 2% to 20%, 10% to 40%, 0.1% to 5%, 0.1% to 5%, and 0.1% to 5%, respectively.

[0020] Preferably, the concentration of selenocystamine in step (2) is 0.05-10 mg / mL.

[0021] More preferably, the concentration of selenocystamine in step (2) is 0.05-0.5 mg / mL.

[0022] Preferably, the stirring time in step (2) is 24 to 36 hours;

[0023] Preferably, the UV curing time in step (2) is 1 to 10 minutes.

[0024] Preferably, the thickness ratio of the GPS hydrogel and the TPU / PCL electrospinning membrane in step (3) is (0.1-10): (0.1-10).

[0025] Further preferably, in step (3), the thickness ratio of the GPS hydrogel and the TPU / PCL electrospinning membrane is (4-6): (2-4).

[0026] Preferably, the thickness of the GPS hydrogel in step (3) is 0.1 to 10 mm; the thickness of the TPU / PCL electrospinning membrane is 0.1 to 10 mm.

[0027] Preferably, the drying temperature in step (3) is 20-30° C. and the drying time is 4-10 hours.

[0028] The present invention provides an elastic adhesive bandage for catalyzing the release of nitric oxide, which is prepared by the above-mentioned preparation method.

[0029] The present invention provides an application of the elastic adhesive bandage that catalyzes the release of nitric oxide in the preparation of an extravascular stent. The elastic adhesive bandage that catalyzes the release of nitric oxide provides mechanical support to guide a more stable blood flow curve when blood transitions from arteries to veins, and can effectively inhibit venous intimal hyperplasia after coronary artery bypass grafting and arteriovenous fistula surgery, thereby improving the patency of blood vessels.

[0030] The elastic fiber membrane prepared by electrospinning of the present invention can not only provide good compliance to support the higher flow rate required for hemodialysis, promote the maturation of arteriovenous fistula, but also prevent postoperative adhesion. The adhesive hydrogel part is not only a good carrier of the drug, but also can fit closely with the blood vessel to provide effective mechanical support. In addition, the drug release is concentrated around the target blood vessel, and this drug release method is more accurate and has more advantages than the traditional systemic drug delivery. Adding selenocystamine to the hydrogel can catalyze the nitric oxide donor in the body to produce nitric oxide, thereby inhibiting the migration of smooth muscle cells. The elastic adhesive bandage that catalyzes the release of nitric oxide is used for external support at the arteriovenous fistula to promote the maturation of the fistula, reduce intimal hyperplasia, and improve the patency of blood vessels.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0032] (1) The elastic fiber membrane prepared by electrospinning in the present invention can not only provide good compliance to support the higher flow rate required for hemodialysis and promote the maturation of arteriovenous fistula, but also prevent postoperative adhesion.

[0033] (2) The adhesive hydrogel part of the present invention is not only a good carrier of drugs, but also can fit closely with blood vessels to provide effective mechanical support. In addition, the drug release is concentrated around the target blood vessels. This drug release method is more accurate and has more advantages than traditional systemic drug delivery.

[0034] (3) The addition of selenocystamine to the hydrogel of the present invention can catalyze the nitric oxide donor in the body to produce nitric oxide, thereby inhibiting the migration of smooth muscle cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the application of the elastic adhesive bandage for catalyzing the release of nitric oxide in the arteriovenous fistula (the outer side is an electrospinning membrane).

[0036] Figure 2 This is a scanning electron microscope image of the TP-GPS elastic adhesive bandage of Example 1.

[0037] Figure 3 1 and 2 are stress-strain curves of the TPU / PCL electrospun fiber membranes of Examples 1 and 2.

[0038] Figure 4 The wet stress-strain curves of the TPU / PCL electrospun fiber membranes of Examples 1 and 2.

[0039] Figure 5 1 and 2 are stress-strain curves of the TP-GPS elastic adhesive bandages of Examples 1 and 3.

[0040] Figure 6 This is a characterization diagram of the adhesion performance of the TP-GPS elastic adhesive bandage of Example 1 to biological and non-biological products.

[0041] Figure 7 Graph showing the lap shear strength of the TP-GPS elastic adhesive bandages of Examples 1 and 3 on wet pig skin.

[0042] Figure 8 Graph showing the interface toughness of the TP-GPS elastic adhesive bandages of Examples 1 and 3 on wet pig skin.

[0043] Fig. 9 This is a characterization diagram of nitric oxide production by the TP-GPS elastic adhesive bandage of Example 1 and Example 4. DETAILED DESCRIPTION

[0044] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0045] The present invention provides a method for preparing an elastic adhesive bandage for catalyzing nitric oxide, comprising the following steps:

[0046] (1) Preparation of thermoplastic polyurethane (TPU) / polycaprolactone (PCL) elastic electrospinning membrane

[0047] Thermoplastic polyurethane (TPU) and polycaprolactone (PCL) were placed in an oven for drying in advance. According to experimental requirements, a certain weight (8% to 30%) of TPU and PCL was weighed and dissolved in hexafluoroisopropanol (HFIP). After stirring for 24 hours, the uniformly dissolved solution was placed in a syringe for electrospinning.

[0048] The electrospinning parameters were set as follows: blunt stainless steel needle: 20G-22G; electrospinning speed: 0.5-4mL / h; collector distance: 5-30cm; voltage: 10-20kV; temperature: 10-35°C; humidity: 20-60%; collector speed: 100-1000rpm.

[0049] The obtained TPU / PCL electrospun membrane was dried in a vacuum oven at room temperature for 24 h to remove excess solvent.

[0050] (2) Preparation of gelatin / polyacrylic acid / selenocystamine (GE / PAA / SeCA) adhesive hydrogel

[0051] 2% to 20% (w / w) gelatin, 10% to 40% (w / w) acrylic acid, 0.1% to 5% (w / w) acrylic acid N-hydroxysuccinimide ester, 0.1% to 5% (w / w) polyethylene glycol diacrylate, and 0.1% to 5% (w / w) (2,4,6-trimethylbenzoyl) diphenylphosphine oxide are dissolved in deionized water, stirred for 24 hours, and then selenocystamine is added, wherein the selenocystamine content is 0.05 to 10 mg / mL. The solution is poured into a polytetrafluoroethylene mold and cured by ultraviolet light for 1-10 minutes to obtain GPS hydrogel.

[0052] (3) Preparation of elastic adhesive bandage that catalyzes the release of nitric oxide

[0053] The GPS hydrogel was attached to the electrospun membrane and placed in an oven to dry and remove part of the moisture to obtain the elastic adhesive bandage TP-GPS that catalyzes nitric oxide.

[0054] The schematic diagram of the application of the elastic adhesive bandage for catalyzing the release of nitric oxide prepared by the present invention for arteriovenous fistula is shown in FIG. Figure 1 .

[0055] Example 1

[0056] A method for preparing an elastic adhesive bandage for catalyzing the release of nitric oxide comprises the following steps:

[0057] (1) Preparation of thermoplastic polyurethane (TPU) / polycaprolactone (PCL) elastic electrospinning membrane

[0058] Thermoplastic polyurethane (TPU) and polycaprolactone (PCL) were placed in an oven for drying in advance. According to experimental requirements, TPU and PCL with a total concentration of 8% (w / w) were weighed and dissolved in hexafluoroisopropanol (HFIP). The mass ratio of TPU to PCL was 3:1. After stirring for 24 hours, the uniformly dissolved solution was placed in a syringe for electrospinning.

[0059] The electrospinning parameters were set as follows: blunt stainless steel needle: 22G; electrospinning speed: 2 mL / h; collector distance: 10 cm; voltage: 15 kV; temperature: 25°C; humidity: 40%; collector speed: 300 rpm.

[0060] The obtained TPU / PCL electrospun membrane was dried in a vacuum drying oven at room temperature for 24 h to remove excess solvent, with a thickness of 0.3 mm.

[0061] (2) Preparation of gelatin / polyacrylic acid / selenocystamine (GE / PAA / SeCA) adhesive hydrogel

[0062] 5% (w / w) gelatin, 30% (w / w) acrylic acid, 1% (w / w) AAc-NHS ester, 0.25% (w / w) polyethylene glycol diacrylate, 0.25% (w / w) (2,4,6-trimethylbenzoyl) diphenylphosphine oxide were dissolved in deionized water, stirred for 24 hours, and then selenocystamine was added, wherein the selenocystamine content was 0.15 mg / mL. The solution was poured into a polytetrafluoroethylene mold and cured by UV light for 5 minutes to obtain GPS hydrogel with a thickness of 0.5 mm.

[0063] (3) Preparation of elastic adhesive bandage that catalyzes the release of nitric oxide

[0064] A layer of GPS hydrogel was attached to a layer of electrospun membrane and placed in an oven at 25°C for 6 h to remove some of the moisture to obtain an elastic adhesive bandage TP-GPS that catalyzes the release of nitric oxide with a thickness of 0.8 mm.

[0065] The scanning electron microscope image of the elastic adhesive bandage TP-GPS for catalyzing the release of nitric oxide prepared in this example is as follows: Figure 2 ,It can be seen that the TPU / PCL electrospinning membrane has a good morphology and the GPS hydrogel has a suitable pore size.

[0066] Example 2

[0067] Adjustment step (1) The mass ratios of TPU and PCL are 0:1, 1:3, and 1:1, respectively, and the rest are the same as in Example 1.

[0068] Example 3

[0069] The acrylic acid content in step (2) was adjusted to 20% or 40% (w / w). The rest was the same as in Example 1.

[0070] Example 4

[0071] The selenocystamine contents in step (2) were adjusted to 0 mg / mL, 0.05 mg / mL, and 0.10 mg / mL, respectively, and the rest were the same as in Example 1.

[0072] Performance Testing

[0073] (1) Mechanical properties testing of electrospun fiber membranes

[0074] The TPU / PCL electrospun fiber membrane was cut into rectangular strips of 10 mm × 60 mm. The sample thickness was measured at 5 points on the electrospun fiber membrane, and then the average value was taken. In order to simulate the wet environment in vivo, the wet fiber membrane was soaked in PBS for 24 hours and then taken out. The tensile strength and elongation at break of the fiber membrane were measured on a universal testing machine at a tensile rate of 50 mm / min. The mechanical properties of TP-GPS were characterized in the same way.

[0075]

[0076] (2) Characterization of adhesion performance of TP-GPS elastic adhesive bandage

[0077] The lap shear strength test was performed according to ASTM F2255 and the 180° peel test was performed according to ASTM F2256. The lap shear strength and interface toughness of the bandage on wet pig skin were tested.

[0078] (3) Characterization of NO production

[0079] Hydrogels containing different concentrations of selenocystamine (0.05 mg / mL, 0.1 mg / mL, 0.15 mg / mL) were prepared and placed in PBS containing 10 μM GSNO and 30 μM GSH. They were placed on a 37°C constant temperature shaker to simulate the human body environment to test the release of NO. 50 μL was taken out at different time points and fresh liquid was added. The release of NO in the hydrogel was detected using the Griess nitric oxide detection kit.

[0080] Data analysis

[0081] (1) Mechanical properties testing of electrospun fiber membranes

[0082] The stress-strain curves of the TPU / PCL electrospun fiber membranes of Example 1 and Example 2 are shown in Figure 3 The wet stress-strain curves of the TPU / PCL electrospun fiber membranes of Example 1 and Example 2 are as follows: Figure 4 .

[0083] Depend on Figure 3 and Figure 4It can be seen that after adding TPU, the mechanical properties of the electrospun fiber membrane are improved. Among them, the mechanical properties of the TPU:PCL=3:1 group are the best, with a wet tensile strength of 6.49MPa and an elongation at break of 330.91%, which has good mechanical properties.

[0084] (2) TP-GPS bandage mechanical properties test

[0085] The stress-strain curves of the TP-GPS elastic adhesive bandages of Example 1 and Example 3 are as follows: Figure 5 .

[0086] Depend on Figure 5 It can be seen that the stress-strain curve of the TP-GPS bandage has a certain hysteresis, indicating that the hydrogel layer can dissipate energy when stretched, thereby improving the mechanical properties of the bandage. Among them, the TP-GPS (30%) group has a tensile strength of 6.79MPa and an elongation at break of 489.76%, which has good mechanical properties.

[0087] (3) Characterization of adhesion performance of TP-GPS elastic adhesive bandage

[0088] The adhesion performance of the TP-GPS elastic adhesive bandage of Example 1 to biological and non-biological products is shown in the figure below: Figure 6 The lap shear strength of the TP-GPS elastic adhesive bandage of Example 1 and Example 3 on wet pig skin is shown in FIG. Figure 7 The interface toughness of the TP-GPS elastic adhesive bandage of Example 1 and Example 3 to wet pig skin is shown in FIG. Figure 8 .

[0089] Depend on Figure 6 , Figure 7 and Figure 8 It can be seen that TP-GPS bandage has good adhesion to both biological and non-biological products. The lap shear strength of TP-GPS (30%) group on wet pig skin is 94kPa, and the interface toughness is 392J / m 2 , with good adhesion.

[0090] (4) Characterization of NO production

[0091] The TP-GPS elastic adhesive bandages of Example 1 and Example 4 produce nitric oxide as shown in the figure Fig. 9 .

[0092] Depend on Fig. 9 It can be seen that TP-GPS bandage can successfully catalyze the production of NO. As the content of selenocystamine in the hydrogel increases, the release of NO gradually increases.

[0093] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing an elastic adhesive bandage that catalyzes the release of nitric oxide, characterized in that: The steps include: (1) dissolving thermoplastic polyurethane and polycaprolactone in an organic solvent, stirring and dissolving them uniformly, then electrospinning them, and drying them to obtain a TPU / PCL electrospinning membrane; (2) dissolving gelatin, acrylic acid, acrylic acid N-hydroxysuccinimide ester, polyethylene glycol diacrylate, and (2,4,6-trimethylbenzoyl) diphenylphosphine oxide in water, adding selenocystamine after stirring, and curing with ultraviolet light to obtain GPS hydrogel; (3) After bonding the GPS hydrogel and the TPU / PCL electrospun membrane, the membrane was dried to obtain an elastic adhesive bandage that catalyzes the release of nitric oxide.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the thermoplastic polyurethane to polycaprolactone in step (1) is (1:10) to (10:1); The total mass percentage concentration of the thermoplastic polyurethane and polycaprolactone in step (1) is 8% to 30%.

3. The preparation method according to claim 1, characterized in that: The electrospinning parameters of step (1) are: blunt stainless steel needle: 20G-22G; electrospinning speed: 0.5-4mL / h; collector distance: 5-30cm; voltage: 10-20kV; temperature: 10-35°C; humidity: 20-60%; collector speed: 100-1000rpm.

4. The preparation method according to claim 1, characterized in that: The organic solvent in step (1) is hexafluoroisopropanol; The stirring time in step (1) is 24 to 36 hours; The drying temperature in step (1) is room temperature and the drying time is 24 to 36 hours; the drying is vacuum drying.

5. The preparation method according to claim 1, characterized in that: The mass percentage concentrations of gelatin, acrylic acid, N-hydroxysuccinimide acrylic acid, polyethylene glycol diacrylate, and (2,4,6-trimethylbenzoyl) diphenylphosphine oxide in step (2) are 2% to 20%, 10% to 40%, 0.1% to 5%, 0.1% to 5%, and 0.1% to 5%, respectively.

6. The preparation method according to claim 1, characterized in that: The concentration of selenocystamine in step (2) is 0.05-10 mg / mL.

7. The preparation method according to claim 1, characterized in that: The stirring time in step (2) is 24 to 36 hours; The UV curing time in step (2) is 1 to 10 minutes.

8. The preparation method according to claim 1, characterized in that: The thickness ratio of the GPS hydrogel and the TPU / PCL electrospinning membrane in step (3) is (0.1-10): (0.1-10).

9. An elastic adhesive bandage for catalyzing the release of nitric oxide prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the elastic adhesive bandage for catalyzing the release of nitric oxide as claimed in claim 9 in the preparation of an extravascular stent.